Evolution of Zn Species on Zn/HZSM‐5 Catalyst under H2 Pretreated and its Effect on Ethylene Aromatization. Issue 16 (18th July 2019) - Gao, Jie; Wei, Chunlei; Dong, Mei; Wang, Guofu; Li, Zhikai; Qin, Zhangfeng; Wang, Jianguo; Fan, Weibin
Abstract: Aromatization reaction is of importance in producing aromatics, accompanied by the generation of abundant H2, which may influence the reaction by interacting with the catalyst. In this work, Zn‐containing ZSM‐5 prepared by impregnation was treated in H2 atmosphere at different temperatures, and the evolution in structure, acidity, and Zn species distribution were studied. The catalyst's performance in ethylene aromatization was also evaluated. The results show that the H2 atmosphere enabled the reconstruction of ZnO microparticles and the reformation of Brønsted acid sites on Zn/HZSM‐5 below 200 °C. At an elevated temperature (300 °C), Zn + species were produced by the reduction of [ZnOZn] 2+ as confirmed by in‐situ Zn K ‐edge extended X‐ray absorption fine structure (EXAFS) study and density functional theory (DFT) calculation. After H2 pretreatment at 300 °C, the increase in the amount of ZnOH + species increased the selectivity of Zn‐containing ZSM‐5 for aromatics from 62 % to 67 %. Abstract : It's in the atmosphere ! The H2 atmosphere enabled the reconstruction of ZnO species and the reformation of Brønsted acid sites between 100 °C and 200 °C. Zn + species were produced from the reduction of [ZnOZn] 2+ as detected at elevated temperature (300–500 °C). An increase in the amount of ZnOH + species in the presence of H2 at 300 °C considerably enhances the catalyst's selectivity for aromatics.